METODE KARMARKAR SEBAGAI ALTERNATIF PENYELESAIAN MASALAH PEMROGRAMAN LINEAR - Bayu Prihandono; Meilyna Habibullah; Evi Noviani (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
Linear programming is a tool for completing an activity plan that has been established in a mathematical model for the desired goal to be achieved. This study aims to introduce how to solve linear programming problems using Karmarkar method. In the Karmarkar method, the linear programming problem is written in a special form called the canonical form of Karmarkar. If there are standard linear programming problems will be solved by Karmarkar method, then the problem must first be converted into Karmarkar canonical form. How the Karmarkar method works starts from the determination of the starting point based on the number of variables, followed by the calculation of radius, the completion range, and the value of the termination criteria. Iterations on the Karmarkar method can be stopped if the value of the objective function has satisfied the condition less than the predefined stop criteria, so the optimum solution point has been obtained.